Design of a dietary intervention to assess the impact of a gluten-free diet in a population with type 1 Diabetes and Celiac Disease - Assor, Esther; Marcon, Margaret A; Hamilton, Natasha; Fry, Marilyn; Cooper, Tammy; Mahmud, Farid H (Université d'Ottawa | University of Ottawa, 2015)
Abstract Background Celiac Disease occurs at a 5–10 fold greater prevalence in patients with type-1 diabetes (T1D), despite this increased risk, there is limited objective evidence regarding the impact of a Gluten-Free Diet (GFD) in the large proportion of asymptomatic (30–70 %) patients with both autoimmune diseases. Given the requirements and intricacies inherent to each condition, we describe the rationale and design a dietary curriculum specifically addressing the educational requirements for children and adults with CD and diabetes as part of the CD-DIET Study. Methods and design The CD-DIET Study (Celiac Disease and Diabetes - Dietary Intervention and Evaluation Trial) is a multicenter randomized controlled trial aimed at evaluating the safety and efficacy of a GFD in patients with asymptomatic celiac disease and T1D on key diabetes and patient-centered outcomes. Discussion Key dietary components of the trial include a description and evaluation of food consumption patterns including glycemic index and glycemic load, novel assessments of gluten quantification, and objective and subjective measures of GFD adherence. This dietary curriculum will establish rigorous guidelines to assess adherence and facilitate evaluation of a GFD on metabolic control, bone health and patient quality of life in patients with CD and diabetes. Trial registration Number NCT01566110 . Date of Registration: March, 2012.